2021
DOI: 10.1177/1043454221992303
|View full text |Cite
|
Sign up to set email alerts
|

Siblings Dealing with Pediatric Cancer: A Family- and Context-oriented Approach

Abstract: Background: Pediatric cancer is a severe life-threatening disease that poses significant challenges to the life of the siblings. Based on the social ecology model, the current study is aimed at exploring the association between intrafamilial (family functioning, family support) and contextual (network support) resources, and the individual adjustment of siblings facing cancer in their brother/sister. Methods: Participants were 81 siblings of children with leukemia or non-Hodgkin lymphoma. The mean siblings’ ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…32,33 Van Schoors et al found that siblings supported by the network external to the family unit, as occurred with the Captains, reported lower levels of loneliness and better emotional involvement in the illness process. 34 A key contribution to the success of the programme lies in its interprofessional collaborative approach; this expands 'Captains on Call' beyond many existing similar programs of distraction and procedural support in paediatric hospitals which may be less integrated into care. Key elements of the programme, including education for the Captains, regular communication between the healthcare teams and a reflective practice cycle, coincides with the World Health Organisation's (WHO) framework for action on collaborative practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Van Schoors et al found that siblings supported by the network external to the family unit, as occurred with the Captains, reported lower levels of loneliness and better emotional involvement in the illness process. 34 A key contribution to the success of the programme lies in its interprofessional collaborative approach; this expands 'Captains on Call' beyond many existing similar programs of distraction and procedural support in paediatric hospitals which may be less integrated into care. Key elements of the programme, including education for the Captains, regular communication between the healthcare teams and a reflective practice cycle, coincides with the World Health Organisation's (WHO) framework for action on collaborative practice.…”
Section: Discussionmentioning
confidence: 99%
“…Van Schoors et al. found that siblings supported by the network external to the family unit, as occurred with the Captains, reported lower levels of loneliness and better emotional involvement in the illness process 34 …”
Section: Discussionmentioning
confidence: 99%
“…Though mortality in pediatric oncology has significantly declined, the profound impact of cancer diagnosis and subsequent treatment cannot be overlooked. Reported challenges across the pediatric cancer continuum include but are not limited to treatment-related symptoms and side effects [ 3 ], psychological morbidity [ 4 ], challenged transition to adult medical care [ 5 ], impaired family function [ 6 ], social isolation [ 7 ], etc. However, these children’s and their families’ varied needs are not always fully recognized and addressed in clinical practice throughout their cancer journey.…”
Section: Introductionmentioning
confidence: 99%
“…Há evidências de que o diagnóstico e tratamento do câncer influencia o ajustamento psicológico dos filhos saudáveis (Van Schoors et al, 2021) e que irmãos de crianças com câncer pode apresentar mais problemas emocionais e comportamentais em consideração à mudança de rotina, convivência com a doença do irmão e questões envolvendo o luto (Paul et al, 2023).…”
unclassified